Lightwave-reinforced stem cells with enhanced wound healing efficacy - Kim, Y.-J.; Jeon, H.R.; Kim, S.-W.; Kim, Y.H.; Im, G.-B.; Im, J.; Um, S.H.; Cho, S.M.; Lee Ju-Ro; 김한영; Joung, Y.K.; Kim, D.-I.; et al. (SAGE-Hindawi Access to Research, 2021)
Comprehensive research has led to significant preclinical outcomes in modified human adipose-derived mesenchymal stem cells (hADSCs). Photobiomodulation (PBM), a technique to enhance the cellular capacity of stem cells, has attracted considerable attention owing to its effectiveness and safety. Here, we suggest a red organic light-emitting diode (OLED)-based PBM strategy to augment the therapeutic efficacy of hADSCs. In vitro assessments revealed that hADSCs basked in red OLED light exhibited enhanced angiogenesis, cell adhesion, and migration compared to naive hADSCs. We demonstrated that the enhancement of cellular capacity was due to an increased level of intracellular reactive oxygen species. Furthermore, accelerated healing and regulated inflammatory response was observed in mice transplanted with red light-basked hADSCs. Overall, our findings suggest that OLED-based PBM may be an easily accessible and attractive approach for tissue regeneration that can be applied to various clinical stem cell therapies.